Challenges of Teacher Autonomy for Professional Competence - Kadel, Purna Bahadur (Interdisciplinary Research in Education, 2021)
Teacher autonomy is essential for their professional competence. Unless they are accountable at their profession, there will not be any positive output in the domain of teaching and learning.  The main objectives of this study were to explore the teachers' perceptions on the impact of teacher autonomy in enhancing their professional competences, to identify how far the level of teacher autonomy affects the professional competences of the teachers, and to investigate the existing practices of teacher autonomy at Tribhuvan University. The phenomenological research design was adopted to accomplish this study. Ten English teachers at least 2 from each of 5constituent colleges of Tribhuvan University were selected as a sample using purposive non-random sampling procedure to collect data. Semi-structured in-depth interview and classroom observations were administered as tools to elicit data to address the objectives of this study. The findings were obsolete of teaching and learning activities and classroom management due to the lack of online digital books and articles in the library, lack of blended between online Moodle and face to face mode of pedagogy, lack of technological pedagogical and content knowledge, no teacher autonomy in curriculum designing, and no grants for travelling and lack of daily allowances to teachers to attend the conference, seminar, and workshop at home and abroad.